Multilevel Spinal Combined Subdural/Subarachnoid Hemorrhage Resulting in Paraplegia: An Unusual Complication of Kyphoplasty - von der Brelie, C.; Fiss, I.; Rohde, V. (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2019)
Background Paraplegia due to spinal combined subdural/subarachnoid hemorrhage is an extremely rare complication following percutaneous spinal augmentation procedures.Methods A 63-year-old male patient presented with severe neurologic decline (paraplegia with sensory and autonomic dysfunction) resulting from a multilevel spinal subarachnoid hemorrhage shortly after bilateral kyphoplasty.Results Reduction of intrathecal pressure via multiple dural and arachnoidal incisions and removal of the hematoma resulted in a good neurologic recovery with surgical decompression even though evacuation was performed with a significant delay after the onset of neurologic worsening.Conclusion Spinal augmentation procedures should only be performed in a setting where management of complications can also be diagnosed and performed. Robot-assisted or navigation-assisted pedicle perforation should be considered because complications can be reduced significantly.
Keywords: kyphoplasty; complication; paraplegia; spinal subarachnoid hemorrhage